Effect of intravenous and intra-cuff magnesium sulphate on post-extubation tracheal morbidity: a randomised single-blind study - Darkwa. E.O.; Vanderpuye. N.M.; Essuman. R.; et al. (Journal of Anesthesia, Analgesia and Critical Care, 2025)
Background Post-extubation sore throat (PEST), cough, and hoarseness are common complications of tracheal intu bation. Several agents and techniques have been postulated to reduce their occurrence. Aim This study sought to compare the effects of intravenous and intra-cuff magnesium sulphate on the incidence and severity of PEST, cough and hoarseness of voice. Materials and methods This was a randomised single-blind study involving 90 surgical patients requiring endotra cheal intubation. Patients were randomised into 3 groups: A (control), B (intra-cuff magnesium sulphate) and C (intravenous magnesium sulphate). Participants in Group A had the endotracheal tube cuff (ETTc) inflated with air to a pressure of 25 cmH2O whilst those in Group B had the ETTc inflated with 2 g of magnesium sulphate solution and the pressure adjusted to 25 cmH2O with top-ups of 0.9% normal saline. Participants in Group C had the ETTc f illed with air to a pressure of 25 cmH2O and received 2 g of intravenous magnesium sulphate in 20 ml of 0.9% normal saline perfused over 10 min immediately prior to the induction of general anaesthesia. The occurrence of PEST, cough and hoarseness of voice were recorded at 0, 4, 8, 12 and 24 h after surgery. Results The incidence of PEST on swallowing in the intra-cuff magnesium sulphate group compared to the intrave nous magnesium sulphate group at 4, 8, and 12 h post-operatively were 51.7% vs 12.5%, 51.7% vs 18.8% and 51.7% vs 21.9% respectively. Compared to intra-cuff magnesium sulphate, intravenous magnesium sulphate significantly reduced the incidence and severity of PEST during swallowing at 4, 8, and 12 h. The incidence of PEST at rest in the intra-cuff magnesium sulphate group compared to the intravenous magnesium sulphate group at 0, 4, 8, 12 and 24 h post-operatively were 13.8% vs 9.4%, 20.7% vs 6.3%, 17.2% vs 6.3%, 13.8% vs 3.1% and 13.8% vs 3.1% respectively. Compared to intra-cuff magnesium sulphate, intravenous magnesium sulphate reduced the incidence of PEST at rest, though this was not statistically significant over first 24 h postoperative period. Intravenous magne sium sulphate had significantly lower PEST severity scores at rest at 12 h only compared to intra-cuff magnesium sulphate. There was no statistically significant difference in the incidence and severity of cough and hoarseness between the study groups.Conclusion Intravenous magnesium sulphate given at induction was found to be better compared to intra-cuff magnesium sulphate in lowering the incidence and severity of post-extubation sore throat on swallowing but not at rest. However, it does not significantly reduce the incidence or severity of post-extubation cough or hoarseness.
Research Article
Keywords: Magnesium sulphate; Intravenous; Extubation